Organization and Regulation of Fencing in the Realm of France in the Renaissance - Dupuis Olivier (Acta Periodica Duellatorum, 2014)
During the nineteenth century, many sources were published about the regulation of fencing in Renaissance France. Comparing those sources shows significant though incomplete uniformity in the formalities observed in the training of students of fencing, particularly in the process followed by the neophyte in his passage to mastery of the art of defence.